Severe pertussis and hyperleukocytosis: is it time to change for exchange?. Issue 6 (16th December 2013) - Kuperman, Amir; Hoffmann, Yoav; Glikman, Danny; Dabbah, Husein; Zonis, Zeev
<x xml:space="preserve">Abstract</x> Background Pertussis is an important cause of infant death worldwide and continues to be a public health concern even in countries with high vaccination coverage. Severe (critical) pertussis with hyperleukocytosis is a severe form of the disease with up to 80% mortality rate. Attempts have been reported to reduce the white blood cell burden by exchange transfusion (ET) with conflicting conclusions. Case Report We report a case of critical pertussis in a neonate who was treated with ET, in view of a comprehensive literature review. Results The patient was discharged without any sequelae. Conclusion ET should be considered in all infants suffering from critical pertussis and hyperleukocytosis, even in secondary care community hospitals.